2002
DOI: 10.1080/00926230290001547
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Sexuality of Opiate Addicts

Abstract: The influence of heroin use on sexual behavior was studied in individuals attending a drug abuse program in Porto, Portugal. As we expected, drug abuse was found mainly to adversely affect sexual behavior. A minority of patients reported improvement in sexual behavior with heroin use. Almost all patients remained sexually active and took no special precautions to prevent sexually transmitted diseases. Some patients reported heroin-related sexual effects to be a motivating factor for ceasing drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 19 publications
4
44
0
4
Order By: Relevance
“…Besides, knowing the drug-related sexual effects may be a motivation for some abusers to cease drug abuse. 42 Gaps are supposed to exist in the research because most of previous studies about the impact of illicit drugs on sexual function adopted simple questions to evaluate sexual function, lacked controls and were based on small case numbers. 40 …”
Section: Illicit Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, knowing the drug-related sexual effects may be a motivation for some abusers to cease drug abuse. 42 Gaps are supposed to exist in the research because most of previous studies about the impact of illicit drugs on sexual function adopted simple questions to evaluate sexual function, lacked controls and were based on small case numbers. 40 …”
Section: Illicit Drugsmentioning
confidence: 99%
“…48,49 Palha and Esteves reported there was a significant decrease in weekly sexual intercourse and masturbatory activity in 101 heroin male addicts compared with healthy controls. 42 Jiann assessed the prevalence of ED (Table 2). 50 Heroin users had the highest prevalence of ED than the others, being attributed to the CNS inhibition and high addiction properties of heroin.…”
Section: ) Opioidsmentioning
confidence: 99%
“…Results indicated that orgasmic dysfunction was moderately prevalent. The research of Palha and Esteves (2002) (43,44), who studied sexual dysfunction among 101 heroin addicts, found that 60% of men in their study had problems achieving orgasm. They also found that 75% of men in their study complained of low libido, 71% reported altered sexual arousal, and 72% had reduced sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on drug users sexuality show high incidence of sexual dysfunction or non satisfying sexual experience (Johnson, Phelps, & Cottler, 2004;Leon & Wexler, 1973;Mintz et al, 1974;Palha & Esteves, 2002). Some authors wonder if a previous clinical condition won't be behind this experience and have a stronger influence than the drug use contingences (La Pera, et al, 2008;Palha & Esteves, 2002).…”
mentioning
confidence: 99%
“…Some authors wonder if a previous clinical condition won't be behind this experience and have a stronger influence than the drug use contingences (La Pera, et al, 2008;Palha & Esteves, 2002). More recently, investigators try to understand to which point the drug use/abuse and sexuality associations are accidentals or the result of an intentional substance use in order to achieve some sexual goals (Bellis et al, 2008;Rawson et al,2002).…”
mentioning
confidence: 99%